Rheumatoid Meningitis - Servioli, Maria J.; Chugh, Chandril; Lee, John; Biller, Jose (Frontiers in Neurology, 2011)
An 80-year-old woman with rheumatoid arthritis had gait difficulties and frequent falls. MRI of the brain showed an extra-axial enhancing lesion overlying the right frontal-parietal cortex, that progressively extended to the contralateral side. This was accompanied by further decline in her functional status. We discuss the diagnostic and therapeutic approach of a pachy-leptomeningeal process in a rheumatoid patient.